Forty ways to think about architecture : architectural history and theory today - Borden, Iain; Fraser, Murray; Penner, Barbara, 1970- (Chichester, West Sussex, United Kingdom : Wiley, 2014)
How do we think about architecture historically and theoretically? Forty Ways to Think about Architecture provides an introduction to some of the wide-ranging ways in which architectural history and theory are being approached today. The inspiration for this project is the work of Adrian Forty, Professor of Architectural History at the Bartlett School of Architecture, University College London (UCL), who has been internationally renowned as the UK's leading academic in the discipline for 40 years. Forty's many publications, notably Objects of Desire (1986), Words and Buildings (2000) and Co.
Front Matter -- How To Write About Buildings? / Andrew Saint -- Pevsner vs Colomina: Word and Image on the Page / Anne Hultzsch -- Smooth and Rough: Tactile Brutalism / Anthony Vidler -- Homely Affinities / Barbara Penner -- On Regeneration / Ben Campkin -- Fresh Reactions to St Paul's Cathedral / Brian Stater -- Photographs and Buildings (mainly) / Briony Fer -- Stirling's Voice: A Detailed Suggestion / David Dunster -- Carte Blanche? / Davide Deriu -- Buildings: A Reader's Guide / Eleanor Young -- The City and the Event: Disturbing, Forgetting and Escaping Memory / Griselda Pollock -- The Most Modern Material Of Them All ... / Hilde Heynen -- Things that People Cannot Anticipate: Skateboarding at the Southbank Centre / Iain Borden -- Truth, Love, Life: Building with Language in Prague Castle under Masaryk / Irena Zantovska Murray -- Le Corbusier: Lies, Damned Lies and Statistics / Jan Birksted -- During Breakfast / Jane Rendell -- [American] Objects of [Soviet] Desire / Jean-Louis Cohen -- Words and Buildings / Jeremy Melvin -- Slow Hard Look / Jeremy Till -- Topography, Biography and Architecture / Joe Kerr -- Of Character and Concrete: The Historian's Material / John Macarthur -- Spectres of Marx in City X / Jonathan Charley -- History by Design / Jonathan Hill -- Angel Place: A Way In to Dickens's London / Kester Rattenbury -- On Sachlichkeit: Some Additional Remarks on an Anglo-German Encounter / Laurent Stalder -- Double Vision / Mark Swenarton -- Modernism / Mary Mcleod -- Yes, And We Have No Dentists / Michael Edwards -- Reyner Banham's Hat / Murray Fraser -- Situated Architectural Historical Ecologies / Peg Rawes -- Objects / Penny Sparke -- Richard Llewelyn Davies, 1912-1981: A Lost Vision for The Bartlett / Sir Peter Hall -- Things Ungrand / Sarah Wigglesworth -- Minor Spaces in Officers' Bungalows of Colonial Bengal / Tania Sengupta -- Memoirs of Adrian / Thomas Weaver -- All That Glitters / Tom Dyckhoff -- A Response to Words and Buildings / Tony Fretton -- Material Culture: Manchester of the East, Le Corbusier, Eames and Indian Jeans / Victoria Perry -- Mr Mumford's Neighbourhood / William Menking -- Banyan Tree and Migrant Cities: Some Provisional Thoughts for a Strategic Postcolonial Cosmopolitanism / Yat Ming Loo.
Includes index.
Includes bibliographical references and index.
Print version record.
Keywords: Architecture -- Philosophy; Architecture -- Philosophy -- 19th century; Architecture -- Philosophy -- 20th century; Architecture -- Philosophy; ARCHITECTURE -- Adaptive Reuse & Renovation; ARCHITECTURE -- Buildings -- Landmarks & Monuments; ARCHITECTURE -- Professional Practice; ARCHITECTURE -- Reference; Architecture -- Philosophy; Electronic books